1991
DOI: 10.3109/07357909109032795
|View full text |Cite
|
Sign up to set email alerts
|

Recent Outcomes for Patients with Carcinoma of the Lung

Abstract: We undertook a retrospective study of all lung cancer patients diagnosed between 1978 to 1982 and seen at the University of California San Diego affiliated hospitals. There were 390 evaluable patients; the vast majority were men. Overall median survival was 8 months and was similar for all histologic types. Completely asymptomatic patients had a median survival of 20.1 months while symptomatic patients had a median survival of 5-8 months. Retrospective application of the new clinical staging system for lung ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Survival analysis showed that tumour stage, grade and nodal status were strongly associated with prognosis, as seen in several earlier studies [5,10,23], and provides indirect evidence of the validity of our survival data although overall survival data were used. To evaluate the prognostic significance of DNA ploidy alterations, tumours were categorized into those with minor and those with major ploidy aberrations.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Survival analysis showed that tumour stage, grade and nodal status were strongly associated with prognosis, as seen in several earlier studies [5,10,23], and provides indirect evidence of the validity of our survival data although overall survival data were used. To evaluate the prognostic significance of DNA ploidy alterations, tumours were categorized into those with minor and those with major ploidy aberrations.…”
Section: Discussionmentioning
confidence: 70%
“…The prognosis of patients with lung cancer is generally poor [5,23,31]. Some 30% are still operable at the time of diagnosis, and only a minority of them will be definitely cured by surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy is a versatile intervention, as it does not require fitness for surgery or the ability to tolerate chemotherapy, can be tailored to the patient by dose modification, and can be integrated with other treatment options. However, median overall survival with radiotherapy alone is 9 to 11 months, and the 5-year survival rate is disappointingly low, at 3% to 10% [7][8][9][10]. Furthermore, radiotherapy cannot treat the distant micrometastases that are often present at the time of diagnosis.…”
Section: Introductionmentioning
confidence: 94%